Consistent image registration. - Christensen, G.E.
Presents a new method for image registration based on jointly estimating the forward and reverse transformations between two images while constraining these transforms to be inverses of one another. This approach produces a consistent set of transformations that have less pairwise registration error, i.e., better correspondence, than traditional methods that estimate the forward and reverse transformations independently. The transformations are estimated iteratively and are restricted to preserve topology by constraining them to obey the laws of continuum mechanics. The transformations are parameterized by a Fourier series to diagonalize the covariance structure imposed by the continuum mechanics constraints and to provide a computationally efficient numerical implementation. Results using a linear elastic material constraint are presented using both magnetic resonance and X-ray computed tomography image data. The results show that the joint estimation of a consistent set of forward and reverse transformations constrained by linear-elasticity give better registration results than using either constraint alone or none at all.
Keywords: CT; MRI; Consistent image registration; Continuum mechanics laws; Covariance structure; Forward transformation; Iterative estimation; Linear elastic material constraint; Magnetic resonance imaging; Medical diagnostic imaging; Pairwise registration error; Reverse transformation; Topology preservation